2012
DOI: 10.3174/ajnr.a3418
|View full text |Cite
|
Sign up to set email alerts
|

Clopidogrel Hyper-Response and Bleeding Risk in Neurointerventional Procedures

Abstract: BACKGROUND AND PURPOSE:Antiplatelet therapy is associated with decreased ischemic events after neurointerventional procedures. Antiplatelet resistance negates the protective effects of antiplatelet medication, leading to a higher incidence of ischemic events. A possible link between antiplatelet hyper-response and increased hemorrhagic complications has been inadequately investigated. We aimed to examine the correlation between antiplatelet hyper-response and the risk of hemorrhagic complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
61
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(65 citation statements)
references
References 26 publications
1
61
1
1
Order By: Relevance
“…Our findings are similar to those reported by Goh et al 24 in a cohort of 47 patients undergoing various types of neurointerventional procedures also tested with VerifyNow (15% using a Ͼ72% "P2Y12% inhibition" cutoff). Most important, using a PRU cutoff of Ͻ80, we evidenced a conversion to a clopidogrel hyper-response in follow-up testing in 77% of patients who had initially been within the target PRU range in preprocedural testing (using a PRU cutoff of Ͻ60, sixty percent of patients would have exhibited a conversion).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Our findings are similar to those reported by Goh et al 24 in a cohort of 47 patients undergoing various types of neurointerventional procedures also tested with VerifyNow (15% using a Ͼ72% "P2Y12% inhibition" cutoff). Most important, using a PRU cutoff of Ͻ80, we evidenced a conversion to a clopidogrel hyper-response in follow-up testing in 77% of patients who had initially been within the target PRU range in preprocedural testing (using a PRU cutoff of Ͻ60, sixty percent of patients would have exhibited a conversion).…”
Section: Discussionsupporting
confidence: 81%
“…In our cohort, 3 of the 4 patients (75%) with perioperative ICHs were found to have P2Y12 receptor overinhibition with markedly decreased PRU values (0, 2, 10) at the time of or just before the ICH. Similarly, Goh et al 24 also found that P2Y12 receptor overinhibition in the perioperative period placed patients undergoing various types of neurointerventional procedures at significantly increased risk of experiencing major perioperative hemorrhagic complications (43%). A study of 133 coil embolization procedures to treat unruptured cerebral aneurysms reported a 30% rate of periprocedural thromboembolic diffusion-weighted imaging-positive lesions within 72 hours of the intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Up to 66% of patients with cerebrovascular disease have a reduced response to clopidogrel, [8][9][10][11] placing them at higher risk of thrombosis, 12 while 14.9%-38% of patients are hyper-responsive to clopidogrel. 13,14 Differing responses to clopidogrel may be related to CYP2C19 gene polymorphisms. 6,9 Of particular clinical importance are the CYP2C19*2 and CYP2C19*3 alleles, more commonly seen in Asian descent than African and Caucasian descent, which reduce enzyme activity and have been associated with an increased incidence of stent thrombosis in coronary intervention studies.…”
mentioning
confidence: 99%
“…Similarly, Goh et al found that hyperresponse to clopidogrel was associated with higher rates of hemorrhage. 14 Heller et al 15 studied the effect of antiplatelet therapy on thromboembolic events after flow diversion with the PED and found no difference in platelet reactivity between patients with and without infarcts found with MR imaging. Although previous studies found an association between platelet-testing results and neurovascular complications after stent/PED placement, studies have yet to clearly demonstrate that altering antiplatelet regimens on the basis of platelet-testing results leads to improved clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%